O processo de humanização: as bases constitutivas da subjetividade - Farias, Francisco Ramos de (1987)
Taking in consideration this evolutive dynamics, which reaches its summit with the break produced by the language, an analyses was carried out by contents of the records from case-study. Starting posterior out a longitudinal discription, followed by interpretation, categories related to each dimension of the psyche were obtained. These categories, in the transversal aspect, were taken as a support for the explanations of the passage from a state of biological subject to a state of a subject who speaks. The direction of this analyses was given in the first place by the postulation of those dimensions their corresponding aspects and the effecters related to these aspects responsible for this passage, which starts when the mother points out to the subject the limit between the philogenic nucleus and the social historical transformations. From this delimitation, occurs the assmilation of typically human characteristics before the paternal law finally fixes the limits of 'becoming a human being'. Meanwhile, occurrances related to those mentioned dimensions can be observed. Concerning the contents kept out of the symbolization field and excluded from the imaginary matrix, the real is characterized by its specific mechanism: foreclosure. The drive remains with its unthinkable and unnamed character. As for actions resulting from the primal repression, they contribute for the formation of signs not liable to the symbolized, which as a facet of the imaginary, associate with information from the philogenic nucleus relative to the originary fantasies, which are considered as another facet of this dimension. As for the symbolic, the signification founds the human condition resulting from repression proper. In this way, the humanization as explained by the concept of repression in the Freudian metapsychology does not accounts only all aspects concerning the 'human'; since it accounts only for what is imagined as a phantasm or what os symbolically presented. For this, the use of the concept of foreclusure in the Lacanian perspective is justified by the fact that it gives a more complete view of this dynamics. Therefore, those elements not liable to symbolization, as well as those of the drive reality, which are not present in the phantasm context, but which acting as a background, enable the articulation of the symbolic and imaginary contents to make socialization possible. At last, socialization is a process originated in the symbolic that settles in the imaginary, taken as a support. For this purpose, the real and its marginal affect enable the return to the symbolic. From then on, the use of the cultural elements brought about by phantasmagoric activity, can be observed.